An on-chip photon-pair source with negligible two photon absorption. (25th January 2019) - Sugiura, Kenta; Okamoto, Ryo; Zhang, Labao; Kang, Lin; Chen, Jian; Wu, Peiheng; Chu, Sai T.; Little, Brent E.; Takeuchi, Shigeki
Abstract: While photon-pair sources using silicon waveguides have shown great promise, strong two-photon absorption (TPA) may limit their brightness. Recently, high-index contrast doped glass (HICDG) has attracted attention because of its CMOS compatibility and low propagation loss. It is also expected that TPA in HICDG is small, though it has not yet been directly measured by conventionally used CW pumping. In this paper, we report that the estimated genuine coincidence events by photon-pairs increase quadratically as the pump power increased and do not show any saturation behavior up to 100 mW CW pump power.